Challenging the divide? Confronting a dialogue across political margins in a feminist classroom. (November 2018) - Hager, Tamar
My article narrates and theorizes one educational moment of speaking 'across' the social and political margins in a peripheral college on the northern border of Israel. I recognize the academic space as what historian Louise Pratt titled a 'contact zone' where peoples geographically and historically separated meet within radically asymmetrical relations of power. In the Israeli academia, secular Westernized Jewish students and teachers from hegemonic groups interact with students from political and social minorities. Despite continued estrangement and mutual hostility, these encounters at times lead to unexpected moments of multicultural alliances. Feminist critical pedagogies serve to identify and create occasions for such interactions that are missing from most academic locations. However, as I demonstrate in this article, these moments which create potential unforeseen resistance to the existing power structure can easily be overlooked. The article focuses on a moment of pedagogical failure to identify an attempt by two female students to cross national affiliations and overcome mutual hostilities, expressing unforeseen solidarity with each other. Reflecting on the political and social reasons for my failure, I end the article by imagining an attempt at amending the pedagogical damage, giving the two students another chance to express their solidarity.